Feminist Collections, v.4, no.3 (spring 1983) - (:unkn) unknown (My University, 1983)
Subtitle: Women's Studies Library Resources in Wisconsin. 40p.
FROM THE EDITORS: Report on a study of women's studies acquisitions at UW-Whitewater. WHY FEMINIST PRINTERS?: Contributions of feminist printers to feminist publishing and the women's movement, by Jean Engle of Ink Well Press. Listing of women's printshops and typesetting, by Barb Wieser. WOMEN IN PRINT: CANADA: Part II of a report on Canadian feminist periodicals, by Eleanor Wachtel. FEMINIST PUBLISHING: Bread & Roses: A Women's Journal of Issues and the Arts, by Linda Shult. SPECIAL COLLECTIONS: The Leon Kramer Collection of socialist and radical literature (UW-Green Bay), by Marian A. Gould. AUDIO RESOURCES FOR WOMEN'S STUDIES: By Judy Gardner. PERIODICAL NOTES: New Periodicals: Cassandra: Radical Feminist Nurses Newsletter; The Herstreet Journal; Lesbian Contradiction: A Journal of Irreverent Feminism; Minerva: Quarterly Report on Women and the Military; 9to5 Newsletter (National Association of Working Women); Sex Studies Index. Special reports on gender relations and feminist theory; international women's liberation; comparable worth; social-psychological studies of women and change; sexual harassment on campus; women in the west; and women's issues in librarianship. ITEMS OF NOTE: Publications from the University of California-Berkeley Center for the Study, Education and Advancement of Women, the Women's Institute for Freedom of the Press, the Ohoyo Resource Center, and Women & Mathematics Education; plus educational media packets on working women, and a ten-year cumulative index to New Directions for Women. NEW REFERENCE WORKS IN WOMEN'S STUDIES: New guides to: women's autobiographical writings; older women in 20th century America; Black women in America; women in 18th and 19th century America; women in Western European history; women's biography; Jewish women's studies; and women in popular culture. Plus a new index, Studies on Women Abstracts. Reviewed by Susan Searing. BOOK REVIEWS: Women's Studies and Strategies Against Violence: Recent Works on Women's Self-Defense, by Barbara Correll. Women as Peformers and Radicals in the United States, by Barbara Melosh. The Mystery Women: Classic Murder Mysteries by Women Writers, by Joan Ray Yeatman.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews